Violence at work : what everyone should know - Van Fleet, Ella W.; Van Fleet, David D. (Emerald Publishing Limited : IAP - Information Age Publishing, Inc., 2014)
Every day we wake up, send our children to school, go to work, attend sports or other entertainment events, etc. Then suddenly the unexpected happens. This day will not end like yesterday and a thousand other days. Our lives are changed forever. Suddenly we realize how precious and fragile life is, and we question whether we could have done something to prevent this emergency event. We have become accustomed to violence, but we do not need to accept it. Our study of workplace violence, terrorism, and other forms of dysfunctional behavior associated with work suggests that both managers and non-managers would like to reduce the risks associated with violence at the workplace. The book is designed to help do just that. You can be underpaid, overworked, or get fired even though you are performing well. You can be a victim of sabotage or harassment even though--or sometimes because!--you are doing an outstanding job. You can be a victim on company premises of an angry, psychologically impaired, or chemically dependent manager, non-manager, former coworker, spouse, or even a stranger. The violent act you face may have stemmed from coworker interaction, worker-boss relations, a sick corporate environment, or even family problems.Top executives and other managerial and non-managerial personnel clearly need to take steps toward reducing the threat of workplace violence. Numerous studies have been done regarding workplace problems, resulting in numerous books and professional journal articles. Some books, articles, workshops, seminars, and the like proffer general advice to managers. However, virtually all of that advice has come from psychologists, physicians, and lawyers. And very little counsel is provided to non-manager employees on dealing with problems that involve co-workers or managers. What has been lacking is advice that would reduce the threat of workplace violence and therefore (1) reduce stress, (2) enable organizations to develop potential competitive advantages in terms of their personnel and productivity, and (3) guide organizational personnel in their efforts to solve problems before they culminate in violent actions. This book fills that need. We believe it is the first to offer both general and specific information and advice from a managerial point of view. The authors have spent their careers intimately involved with the practice, teaching, and research on management and organizations.
Keywords: Violence in the workplace.; Business & Economics -- Human Resources & Personnel Management.; Personnel and human resources management.; elektronické knihy; electronic books